Analysis of corrosion behaviour of carbon steel in a Qatari GTL plant process water. (September 2022) - Sobaih, Mariem; Talkhan, Ahmed Gomaa; Ewis, Dina; Benamor, Abdelbaki; Nasser, Mustafa; Al-Rawashdeh, Ma'moun; Okonkwo, Paul C.
Abstract: Internal Corrosion in tubing, piping, and process system is a huge challenge to the oil and gas facilities. Severe corrosion problems in the carbon steel pipelines are caused by the high corrosive produced water, leading to significant threats to the humans' safety, and operation quality, and causing economic losses. In this study, the effect of the process water from the Qatar Shell GTL plant on the corrosion of SAE-1040 carbon steel was studied by using electrochemical measurements. The electrochemical measurement was performed utilizing electrical impendence spectroscopy (EIS) and Potentiodynamic polarization techniques. The corrosion behavior of the metal was tested at a variety of temperatures between 293K and 333K and different immersed times up to 3 h. It is reported that the corrosion rate of the carbon steel metal increased as the immersed period and the temperature increased. The behavior was attributed to the presence of cracks, holes, and pitting observed on the corroded steel surface as the immersion time and temperature increased. Scanning Electron Microscopic (SEM), X-ray Diffraction (XRD), Energy-dispersive X-ray (EDX), and X-ray Photoelectron Spectroscopy (XPS) tests were employed to study the surface of the corroded metal samples. The analysis of the corrosion products confirmed the formation of iron oxide (Fe2 O3 ) as the main corrosion product. Highlights: SAE-1040 carbon steel corrosion behavior in GTL process. The effect of solution temperature and the exposure time was investigated. The surface of the corroded metal samples was analyzed. Iron oxide (III) and ferric oxide Fe2 O3 Confirm as the main protective layer.